Flexible social perspective taking in higher education and the role of contextual cues - Wolgast, Anett; Barnes-Holmes, Yvonne (Frontline Learning Research, 2022)
Being able to coordinate the perspectives of oneself and others is likely to be helpful in educational contexts. For example, teachers need flexible social perspective taking to understand their own perspectives and those of their students. Evidence suggests that reading facilitates social perspective taking because it involves readers coordinating social perspectives. However, there is little evidence on actual flexible perspective taking in educational contexts. In the current research, we assumed that the presence of different spatial, temporal, and social cues with regard to (higher) educational contexts would affect flexible social perspective taking performances of prospective psychologists and teachers. Across two different studies, we employed relational frame theory and a within-subject design (n = 44 undergraduate students in Study 1 and n = 176 teacher education students in Study 2). We analyzed the data by Rasch-trees and general linear modeling. The results showed faster responding on flexible spatial and temporal social perspective taking tasks, involving a fictional college course in “English” rather than “statistics” (Study 1). In Study 2, the results suggested greater accuracy on flexible spatial and temporal social perspective taking tasks involving spatial rather than temporal relations (Study 2). The results shed some light on the integration of different approaches for research on understanding the relevance of flexible social perspective taking in educational contexts. Flexible spatial and temporal social perspective taking may be of benefit to both students in higher education and teachers in school education.